Identification of Acute Respiratory Infection Patients Using RP2 Nested Multiplex PCR Test in Jakarta, Indonesia - Dewi Inderiati; Tanty Rachmawaty; Citra Amaniah Anhar (Medical Laboratory Technology Journal, 2023)
Acute Respiratory Infection (ARI) is an acute respiratory disease caused by infectious organisms transmitted between humans. Viruses and bacteria generally cause the cause of ARI infection. Other viruses that can also cause ARI are Influenza, Adenovirus, Enterovirus, and Respiratory Syncytial Virus. This study aims to determine the causes of bacterial or viral ARI infection with RP2 Nested Multiplex RT-PCR. The research methodology is cross-sectional. The sample used was 50 people with purposive sampling technique in patients with ARI who examined bacteria and viruses using RP2 Nested Multiplex RT-PCR. The research was located at the Laboratory of the United States Embassy in Jakarta, Indonesia. The results showed that 26 (52%) men suffered more from ARI patients than 24 women (46%), with the most age group being children, 28 people (56%). The three symptoms that many patients in this study felt were that 40 patients (80%) experienced nasal congestion, 38 patients (76%) experienced fever, and 32 patients (64%) coughed. The results of the organisms in the RP2 nested multiplex RT-PCR examination showed that 100% of the causes of ARI were viruses with the highest prevalence (40%) originating from the Human Rhinovirus/Enterovirus. The reason for ARI in this research is from a virus (100%), so antibiotics are not needed for this patient.